Experimental Study of Glow Discharge Plasma Properties at the middle Distance between Anode and Cathode for Aluminum Electrodes - Radam, Hamid K; Hashoosh, Ahmed K (Al-Nahrain Journal of Science, 2018)
The plasma parameters which have been studied were electron density, Debye shielding, plasma oscillation and electron temperature. The parameters measured by using single probe in glow discharge at different pressure and different gases (air and Argon). The results show that, the density of free electrons is inversely proportional with the pressure because of the recombination process which increases with pressure increasing. Also Debye length decreases when pressure increases and plasma oscillation inversely proportional with the pressure. Finely, the current density in a positive bias voltage applied on the probe was larger than the current density and vice versa.